Preparation of stable MCM-48 tubular membranes - Pedernera, Marisa Noemi (2009)
Stable mesoporous membranes with a cubic structure, based on the MCM-48 material, were successfully prepared on alumina supports by hydrothermal synthesis, starting from sols having both CTABr and TPAOH structure directing agents. The inclusion of a zeolite (MFI-type) precursor during membrane synthesis led to partial zeolite incorporation into the porous structure, giving rise to a hydrothermally stable membrane. The mean pore diameter of the membrane was 2.5 nm, and permeation experiments confirmed that transport across the membrane was governed by Knudsen diffusion and that there were no pinholes. The hydrothermal stability of conventionally prepared (MCM-48) and partly zeolitized (MCMZ) powders was studied. Unlike MCM-48 samples (whose surface area sharply decreased after the hydrothermal treatment), the MCMZ surface area remained constant (1031 m2/g before and 1009 m2/g after the hydrothermal treatment), indicating a high hydrothermal stability. MCMZ membranes were tested in the gas phase separation of binary organic (cyclohexane, benzene and n-hexane)/O2 mixtures. A maximum selectivity of 124 was obtained for the separation of cyclohexane/O2 mixtures. The selective permeation of the organic compound was made possible by specific interactions between the organic molecules and the mesoporous host materials, and/or by capillary condensation within the membrane pores.